Bulging Behavior of Thin-walled Welded Low Carbon Steel Tubes - XIE Wen-cai; YUAN Shi-jian (Cailiao gongcheng, 2017)
In order to investigate the deformation behaviour of welded tubes during hydraulic bulging process,the hydraulic bulging tests of thin-walled welded low carbon steel tubes (STKM11A) were conducted on the tube hydroformability testing unit.The thickness distribution,profiles of bulging area and the strain distribution were all obtained.Results show that the thickness reduction of weld zone is just 2.4%-5.5% while its effective strain is just 0.05-0.10,which is very small and negligible compared with the parent material and means that just the geometric position of weld zone is changed with the continuous bulging.The thinnest points are located on the both sides of weld seam symmetrically and the angle between the thinnest point and weld seam is about 30°,at which the necking has been occurred.When the length of bulging area increases,the fracture pressure,the thickness reduction and the ultimate expansion ratio all decrease,and the profile of the bulging area gradually steps away from the elliptical model which is powerless for the ratio of length to diameter up to 2.0.Moreover,the strain state of the tube is transformed from biaxial tension to plane strain state with the increasing length of bulging area,on the basis of this the forming limit diagram of welded STKM11A steel tubes can be established.